A Systematic Review of How Circular Economy Models Are Operationalized in the Hospitality Industry - Warta Sumirat; Muhammad Fadhli Ramadhan; Erza Mutaqin (Journal of Tourism, Hospitality and Travel Management, 2025)
The transition to a Circular Economy (CE) is increasingly positioned as a strategic imperative for the hospitality industry to decouple growth from resource depletion. However, a significant disconnect remains between theoretical ambitions ("rhetoric") and operational realities. This study aims to bridge this gap by critically evaluating how CE models are operationalized in the hotel sector. Adhering to the PRISMA 2020 guidelines, a systematic literature review was conducted in the Scopus database, yielding a final synthesis of 48 empirical studies published between 2020 and early 2025. The analysis reveals a "Circularity Paradox": while adoption is accelerating post-pandemic, operationalization is predominantly characterized by "weak circularity," focusing on linear efficiency measures—such as energy retrofits and downstream waste recycling (3R)—rather than systemic business model innovation. "Strong circularity" practices, such as Product-as-a-Service (PaaS) or adaptive reuse, remain nascent. The study identifies a structural divide where multinational chains leverage "Smart Circularity," whereas Small and Medium Enterprises (SMEs) face an "Implementation Wall" due to prohibitive capital expenditures and a lack of meso-level infrastructure. The findings suggest that moving beyond rhetoric requires a paradigm shift from technical resource efficiency to regenerative sufficiency, necessitating integrated policy support for industrial symbiosis and investment in human capital to bridge the behavioral "Green Gap" among guests and staff.